Independência e cognição pós-AVC e sua relação com a sobrecarga, dor e qualidade de vida dos cuidadores familiares - Caro, Camila Caminha (2015)
Stroke is one of the chronic diseases that cause impairment, mainly motor and cognitive ones, which can compromise the functional capacity, making the subject dependent of care. In this context, it is family s responsibility to take care for the ill individual, assisting him in several everyday activities. The possibility of being a caregiver causes many changes in family dynamics, in the roles and in people's everyday lives. The extended period of care dispensed to the ill individual can also generate overburden and pain and hence threats to the quality of life of caregivers. This study aims to verify the presence of correlations between the level of independence and cognition in subjects with stroke and the level of overburden, pain and quality of life of their family caregivers. We sought to identify if the variables: age of the subject with stroke and caregiver, length of injury, rehabilitation and dispensed care, per capita income, physical, psychological, social and environmental aspects of family caregivers interfere in this relationship. Therefore, we adopted a correlation research with a quantitative approach. The sample consisted of sixty (n = 60) subjects, of which thirty (n = 30) were adults, male, with stroke diagnosis for more than six months and placed in rehabilitation services; and the other thirty (n = 30) their respective family caregivers, who had dispensed care to these individuals for more than six months. To collect data, we proceeded with the application of an (i) Form with data about the subject with stroke, (ii) Mini-Mental Scale and (iii) the Functional the Independence Measure (iv) Form caregiver identification, to (v) Zarit Burden Interview Scale, the (vi) Visual Analogue Scale of Pain and (vii) WHOQOL Bref, and (i), (ii) and (iii) were applied to subjects with stroke and (iv), (v), (vi) and (vii) to their family caregivers. Data analysis is based on a quantitative approach, using three forms of analysis, namely the simple descriptive, factorial and the Pearson correlation coefficient. In results, we presented findings that subjects with higher dependence levels were related to a greater number of cognitive impairment resulting from stroke and the need for further rehabilitation time as well as caregivers of over burdened stroke subjects showed higher levels of pain, with the latter conditions also related to lower levels of quality between them. It s concluded that this research provided important data which can foster new public policies, as well as actions related to Occupational Therapy, especially the ones which include the familiar caregiver.